Sistema de análise de perigos e pontos críticos de controle na indústria de erva-mate: uma visão da nova economia institucional - Lima, Denise Pastore de (2005)
The study evaluates the microbiological physical and chemical hazards existing in the process of mate for chimarrão determining prevention writs to the hazard defining the critical limits the necessary stages of monitoring and the needed registers for the control of the process as the measures of verification of the Critical Points of Control and HACCP Plan The study also focuses the food safety system according to the Institutional New Economy According to NEI the food safety study allows to characterize the integration of the relationships among the institutional environment organizations and the individual In the food case which buyers can not verify themselves the desired quality standards it is necessary to adopt strategies that stand out these characteristics This decision has made public and private institutions to adopt the quality tools as the HACCP system The HACCP system introduction can help the inspection by control organizations and promote the international trade The study was based in the descriptive research in the case study type It points as main microbiological hazards: the coliforms at 45oC mold and Salmonella sp; chemical hazards: herbicides used in the farming; physical hazards: strange substances Fragments the stages of the process considered as Critical Points of Control are the stages of reception of the raw material considered a chemical CPC and the stage of drying considered a microbiological Critical Control Point The limits for these two hazards are the absence of herbicides and the humidity of the product after the drying stage to be 5 to 8 % For that the control of the temperature and the setting time of mate is from necessary in the stage of drying and the control of the raw material in the stage of reception It is concluded that safety of chimarrão involves directly the institutions organizations and consumer?s engagement